2005
DOI: 10.1002/ange.200502668
|View full text |Cite
|
Sign up to set email alerts
|

A Phthalocyanine Clathrate of Cubic Symmetry Containing Interconnected Solvent‐Filled Voids of Nanometer Dimensions

Abstract: Riesenräume! Ein auf Zink[octa(2,6‐diisopropylphenoxy)phthalocyanin] basierendes Clathrat enthält in seiner Struktur solvensgefüllte ungewöhnlich große Hohlräume (>8 nm3; die Packungsanordnung ist gezeigt). Jeder Nanohohlraum ist von einer kubischen Anordnung aus 6 Phthalocyaninmolekülen umschlossen und enthält 18 Wassermoleküle sowie geschätzte 65 Acetonmoleküle, die ohne Ordnungsverlust durch Methanol‐ oder Wassermoleküle ersetzt werden können.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…We changed poor solvent from acetone to n ‐hexane for the crystal growth of 1 with TPFB. Large crystals with a cubic morphology were obtained by the crystallization from a CHCl 3 solution of 1 by diffusing n ‐hexane, and the molecular packing arrangement of 1 in the single crystal [ Pn 3 n space group with 12 molecules of 1 in the unit cell ( a = 3.76 nm)] agreed with the reported structure . The presence of an axial O atom coordinated with the central Zn in the cone‐shaped phthalocyanine core of 1 was also confirmed (Figure S3).…”
Section: Calculated Transition Energies Oscillator Strengths F and supporting
confidence: 72%
See 3 more Smart Citations
“…We changed poor solvent from acetone to n ‐hexane for the crystal growth of 1 with TPFB. Large crystals with a cubic morphology were obtained by the crystallization from a CHCl 3 solution of 1 by diffusing n ‐hexane, and the molecular packing arrangement of 1 in the single crystal [ Pn 3 n space group with 12 molecules of 1 in the unit cell ( a = 3.76 nm)] agreed with the reported structure . The presence of an axial O atom coordinated with the central Zn in the cone‐shaped phthalocyanine core of 1 was also confirmed (Figure S3).…”
Section: Calculated Transition Energies Oscillator Strengths F and supporting
confidence: 72%
“…ZnPcs have been widely studied as photosensitizers for the photochemical production of 1 Δ g O 2 from O 2 as well as for the dye‐sensitized solar cells;, however, there have been no reports on the reactivity of water molecules bounded to the central Zn 2+ in ZnPcs so far. The axial coordination of donor solvents such as acetone and water was confirmed by the single‐crystal X‐ray structural characterization of two ZnPcs having bulky peripheral substituents , . Bench et al reported the stable ligation of two acetone molecules with Zn 2+ in ZnPc bearing bulky perfluoro(isopropyl) units at the peripheral positions of the phthalocyanine ring .…”
Section: Calculated Transition Energies Oscillator Strengths F and mentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, the bulky substituents around the ZnPc ring were changed from 2,6‐diphenyl‐4‐methoxyphenoxy units to 2,6‐diisopropylphenoxy units in order to increase the adsorption density. Symmetrical ZnPc decorated with 2,6‐isopropylphenoxy units prevented π–π stacking of the ZnPcs within the crystals in the cubic morphology reported by McKeown et al 18. The molecular model of PcS18 reveals a small amount of steric crowding around the ZnPc ring compared to PcS17 (Figure 3), and reducing the size of peripheral substituents may lead to close packing of dyes on the TiO 2 surface.…”
Section: Resultsmentioning
confidence: 75%